KETIMPANGAN DAYA SAING ANTARA PELAKU USAHA BESAR DAN UMKM DALAM PASAR MONOPOLI DI KABUPATEN SUMBAWA - Febrian, Sultan; Ilahi, Putri Karunia; Putri, Marzella Adelia; Radiputra, Arya (Pusat Riset dan Publikasi, 2025)
Competition law is an important instrument in maintaining healthy and fair market dynamics, especially in the era of globalization marked by increasingly competitive economic growth. This study aims to examine the competitiveness inequality between Micro, Small, and Medium Enterprises (MSMEs) and big business actors in the context of a monopoly market in Sumbawa District. This study was conducted using a qualitative approach using a literature review method. Data were collected from various sources, such as journals, books, and official reports. The analytical technique used was content analysis, which involved data reduction, data presentation, and drawing conclusions based on the main themes: market access, technology access, and product differentiation. The results of this study indicate a competitive inequality between Micro, Small, and Medium Enterprises (MSMEs) and big businesses actors in monopoly market in Sumbawa District. Big business actors generally have strong structural strengths and networks, which creates significant barriers for MSMEs. Limited market access and technology are the main factors weakening the position of MSMEs. Conversely, big businesses utilize product differentiation strategies and strong distribution networks to dominate local markets. This research recommends policy interventions focused on improving access to technology, capacity training, and expanding distribution networks for MSMEs.